2021
DOI: 10.1186/s12967-021-02964-6
|View full text |Cite
|
Sign up to set email alerts
|

WT1 and ACE mRNAs of blood extracellular vesicle as biomarkers of diabetic nephropathy

Abstract: Background Diabetic nephropathy (DN) has an increasing global prevalence with excessive health expenditure and burden. Exosomal mRNAs regulate intercellular communications and participate in the pathogenesis of various disorders like DN. This study aimed to assess the expression levels of ACE, ELMO1, and WT1 mRNAs in the blood extracellular vesicles (EVs) of DN patients and diabetic patients without nephropathy (DM group) in comparison to healthy controls and investigate their correlations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…However, recent quantitative RNA sequencing of WT1 and ACE mRNAs from blood EVs of DN patients showed upregulated expression of WT1 mRNA and downregulated expression of ACE mRNA in DN patients compared to DM patients and controls. Moreover, WT1 and ACE mRNAs from blood EVs were associated with the severity of albuminuria and showed good diagnostic performance to discriminate DN from DM [41]. This study, in agreement with our study, indicated the important role of mRNA from blood EVs in DN development and also showed that exploring more mRNA profiles of blood EVs in DN will lead to a better understanding of DN pathophysiology and the discovery of alternative biomarkers for DN management.…”
Section: Plos Onesupporting
confidence: 90%
“…However, recent quantitative RNA sequencing of WT1 and ACE mRNAs from blood EVs of DN patients showed upregulated expression of WT1 mRNA and downregulated expression of ACE mRNA in DN patients compared to DM patients and controls. Moreover, WT1 and ACE mRNAs from blood EVs were associated with the severity of albuminuria and showed good diagnostic performance to discriminate DN from DM [41]. This study, in agreement with our study, indicated the important role of mRNA from blood EVs in DN development and also showed that exploring more mRNA profiles of blood EVs in DN will lead to a better understanding of DN pathophysiology and the discovery of alternative biomarkers for DN management.…”
Section: Plos Onesupporting
confidence: 90%
“…It is shown that sACE is significantly related to the infection mechanism of novel coronavirus (SARS-CoV-2) and can be used to diagnose patients with such infection [ 23 ]. sACE can also be used as a serum exosomal messenger RNA (mRNA) indicator to diagnose early diabetic nephropathy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current new biomarkers mainly target diagnoses of inflammation, endothelial damage, fibrosis, endothelial dysfunction, and kidney damage, 141 including TNF-α receptor, 142 intercellular adhesion molecule-1, 143 endostatin, 144 copeptin, 145 kidney injury molecule-1, 146 , 147 monocyte chemoattractant protein-1, 148 and neutrophil gelatinase-associated lipocalins. 149 Extracellular vesicles have recently attracted interest, 150 because they are essentially exosomes and particles 151 that transport miRNA, 152 mRNA, 153 , 154 and proteins, 155 and might serve as early biomarkers of DKD. In addition to individual biomarkers, other approaches such as proteomics, 156 genomics, 157 and metabolomics 158 all play roles in screening, especially in studies of chronic kidney disease (CKD) 159 which can predict the development of proteinuria.…”
Section: Introductionmentioning
confidence: 99%